Pemanfaatan Data Statistik Dapat Memudahkan Pengurus Dalam Menangani Santri Sakit Di Asrama Al-Aziziyah - Moh. Abdul Qohar; Zulia Putri, Armia; Layali Tama, Najwa; Lubabil Fiqri, Hilvi; Rendy Prayogo, Muhammad (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
This article aims to describe the process and results of observation activities for Al Aziziyah dormitory residents who seek to improve the knowledge and skills of Tadris Mathematics Uimsya students and Al Aziziyah dormitory administrators in processing statistical data manually. Observation activities were carried out for 1 (one) month. The stages in observation include observation, planning, implementation and evaluation. This observation activity was proven to produce statistical data with an average of 88 people. From the implementation of this observation, it is known that the observation went smoothly according to plan. However, there are several things that still need to be better designed in carrying out similar activities, including the techniques and methods used in the mentoring process